The impact of nontransparent health communication during the COVID-19 pandemic on vaccine-hesitant people’s perception of vaccines - Wegwarth, Odette; Hertwig, Ralph; Giese, Helge; Fineberg, Harvey V. (Frontiers in Public Health, 2024)
Although transparency is crucial for building public trust, public health communication during the COVID-19 pandemic was often nontransparent. In a cross-sectional online study with COVID-19 vaccine-hesitant German residents (N = 763), we explored the impact of COVID-19 public health communication on the attitudes of vaccinehesitant individuals towards vaccines as well as their perceptions of incomprehensible and incomplete information.We also investigated whether specific formats of public health messaging were perceived as more trustworthy. Of the 763 participants, 90 (11.8%) said they had become more open-minded towards vaccines in general, 408 (53.5%) reported no change, and 265 (34.7%) said they had become more skeptical as a result of public health communication on COVID-19 vaccines. These subgroups differed in how incomprehensible they found public health communication and whether they thought information had been missing. Participants' ranking of trustworthy public health messaging did not provide clear-cut results: the fully transparent message, which reported the benefit and harms in terms of absolute risk, and the nontransparent message, which reported only the benefit in terms of relative risk were both considered equally trustworthy (p = .848). Increased skepticism about vaccines during the COVID-19 pandemic may have partly been fueled by subpar public health communication. Given the importance of public trust for coping with future health crises, public health communicators should ensure that their messaging is clear and transparent.